SINGLE TRAIT ANALYSIS FOR PREWEANING GROWTH TRAITS OF BUCHI SHEEP IN PAKISTAN - M. Akhtar; K. Javed; M. Abdullah (Journal of Animal and Plant Sciences, 2014)
Data on 3,564 Buchi sheep (55 males and 1,296 females; from 1986 to 2010) maintained at Livestock Experiment Station Jugaitpir District Bahawlpur Punjab, Pakistan were analyzed to assess preweaning growth traits and their genetic control. Means±SE were 2.84 ± 0.009 kg for birth weight, 7.64 ± 0.014 kg for weight at around 60 days of age, and 12.55 ± 0.03 kg for weaning weight adjusted to 120 days of age. Variance components corresponding to genetic parameters were estimated with single trait analysis using restricted maximum likelihood (REML) procedures, fitting model included direct additive genetic, maternal additive genetic, maternal permanent environmental effects and correlation between genetic direct and maternal effects by ASREML computer program. Study revealed that all preweaning traits were significantly (P < 0.05) affected by year, sex, interaction between year and season. Direct heritability estimated were 0.194±0.023 for birth weight, 0.20±0.025 for weight adjusted to60 days and 0.153±0.03 for weight adjusted to 120 days of age. Estimation of maternal heritability for birth weight, weight adjusted to 60 days and 120 days of age were 0.132± 0.025, 0.20± 0.028 and 0.12 ± 0.03, respectively. Negative correlation between direct and maternal heritability was estimated for all three preweaning traits (-0.517± 0.06, -1.013± 0.01, - 0.455± 0.004). These results indicate that selecting for improved maternal and/or direct effects in Buchi sheep would generate only slow genetic progress in early growth traits.
Keywords: Buchi sheep; Heritability; Maternal; Preweaning; traits